Metabolic control of resting hemispheric cerebral blood flow is oxidative, not glycolytic - Powers, William J (Nature Publishing Group, 2011)
Although the close regional coupling of resting cerebral blood flow (CBF) with both cerebral metabolic rate of oxygen (CMRO(2)) and cerebral metabolic rate of glucose (CMRglc) within individuals is well documented, there are few data regarding the coupling between whole brain flow and metabolism among different subjects. To investigate the metabolic control of resting whole brain CBF, we performed multivariate analysis of hemispheric CMRO(2), CMRglc, and other covariates as predictors of resting CBF among 23 normal humans. The univariate analysis showed that only CMRO(2) was a significant predictor of CBF. The final multivariate model contained two additional terms in addition to CMRO(2): arterial oxygen content and oxygen extraction fraction. Notably, arterial plasma glucose concentration and CMRglc were not included in the final model. Our data demonstrate that the metabolic factor controlling hemispheric CBF in the normal resting brain is CMRO(2) and that CMRglc does not make a contribution. Our findings provide evidence for compartmentalization of brain metabolism into a basal component in which CBF is coupled to oxygen metabolism and an activation component in which CBF is controlled by another mechanism.